Effects of bark-stripping on the water relations of Quercus suber L - Correia, O. A.; Oliveira, G.; Martins-Loução, M. A.; Catarino, F. M. (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations